Algebraic Expressions Addition: Worksheets, Online Test and Calculators

Algebraic expressions addition worksheets, solved worksheet problems or exercises with step-by-step work, formative assessment as online test, calculator and more learning resources to learn, practice, assess and master the basic math skills of algebra.

Algebraic Expressions Addition
Name Grade School
Date Questions20 Score

1
Add x-y+z=10 and x-y+z=20
2
Add 3x+10y=1 and 3x+4y=18
3
Add 4y+5x=9 and 4y+3x=40
4
Add 5x+12y=34 and 9x+2y=36
5
Add 5m+6n+p=19 and 4m+6n+2p=40
6
Add 6s+7t=2 and s+6t-12=0
7
Add 10y+5z=1 and 2y+3z=23
8
Add 4y+2x-2z=4 and 6x+9y-4z=7
9
Add 9a+8b=0 and 6a+6b=-3
10
Add -2x+2y+z=1 and 5x+3y+2z=7
11
Add 2s-3t=2 and 5s-2t-12=0
12
Add 12y-15z=19 and 12y+13z=30
13
Add 14y+2x-12z=14 and 16x+9y-2z=17
14
Add 9a+8b+c=20 and 6a+6b+2c=-3
15
Add -12x+12y+3z=1 and 5x+13y+12z=70
16
Add 3x+4y-5z=10 and 4x+5y-2z=20
17
Add 3x+10y=1 and 13x+14y=18
18
Add -4y+5x+8z=9 and -4y-3x+2z=40
19
Add 15x+12y=34 and 19x+12y=36
20
Add 15m-16n+3p=19 and 14m-16n+2p=0

Solved Worksheet Problems
Show All Workout
1
Add x-y+z=10 and x-y+z=20
2x-2y+2z=30
Solution
(x-y+z=10) + ( x-y+z=20 )
Variable x terms are   
  (1x) + (1x)
= 2x

Variable y terms are   
  (-1y) + (-1y)
= -2y

Variable z terms are   
  (1z) + (1z)
= 2z

Constant  terms are   
  (10) + (20)
= 30


Hence the Equation is   2x-2y+2z=30
2
Add 3x+10y=1 and 3x+4y=18
6x+14y=19
Solution
(3x+10y=1 ) + ( 3x+4y=18 )
Variable x terms are   
  (3x) + (3x)
= 6x

Variable y terms are   
  (10y) + (4y)
= 14y

Constant  terms are   
  (1) + (18)
= 19


Hence the Equation is   6x+14y=19
3
Add 4y+5x=9 and 4y+3x=40
8y+8x=49
Solution
(4y+5x=9) + ( 4y+3x=40 )
Variable y terms are   
  (4y) + (4y)
= 8y

Variable x terms are   
  (5x) + (3x)
= 8x

Constant  terms are   
  (9) + (40)
= 49


Hence the Equation is   8y+8x=49
4
Add 5x+12y=34 and 9x+2y=36
14x+14y=70
Solution
(5x+12y=34) + ( 9x+2y=36 )
Variable x terms are   
  (5x) + (9x)
= 14x

Variable y terms are   
  (12y) + (2y)
= 14y

Constant  terms are   
  (34) + (36)
= 70


Hence the Equation is   14x+14y=70
5
Add 5m+6n+p=19 and 4m+6n+2p=40
9m+12n+3p=59
Solution
(5m+6n+p=19) + ( 4m+6n+2p=40 )
Variable m terms are   
  (5m) + (4m)
= 9m

Variable n terms are   
  (6n) + (6n)
= 12n

Variable p terms are   
  (1p) + (2p)
= 3p

Constant  terms are   
  (19) + (40)
= 59


Hence the Equation is   9m+12n+3p=59
6
Add 6s+7t=2 and s+6t-12=0
7s+13t=14
Solution
(6s+7t=2) + ( s+6t-12=0 )
Variable s terms are   
  (6s) + (1s)
= 7s

Variable t terms are   
  (7t) + (6t)
= 13t

Constant  terms are   
  (2) + (12)
= 14


Hence the Equation is   7s+13t=14
7
Add 10y+5z=1 and 2y+3z=23
12y+8z=24
Solution
(10y+5z=1) + ( 2y+3z=23 )
Variable y terms are   
  (10y) + (2y)
= 12y

Variable z terms are   
  (5z) + (3z)
= 8z

Constant  terms are   
  (1) + (23)
= 24


Hence the Equation is   12y+8z=24
8
Add 4y+2x-2z=4 and 6x+9y-4z=7
13y+8x-6z=11
Solution
(4y+2x-2z=4) + ( 6x+9y-4z=7 )
Variable y terms are   
  (4y) + (9y)
= 13y

Variable x terms are   
  (2x) + (6x)
= 8x

Variable z terms are   
  (-2z) + (-4z)
= -6z

Constant  terms are   
  (4) + (7)
= 11


Hence the Equation is   13y+8x-6z=11
9
Add 9a+8b=0 and 6a+6b=-3
15a+14b=-3
Solution
(9a+8b=0) + ( 6a+6b=-3 )
Variable a terms are   
  (9a) + (6a)
= 15a

Variable b terms are   
  (8b) + (6b)
= 14b

Constant  terms are   
  (0) + (-3)
= -3


Hence the Equation is   15a+14b=-3
10
Add -2x+2y+z=1 and 5x+3y+2z=7
3x+5y+3z=8
Solution
(-2x+2y+z=1) + ( 5x+3y+2z=7 )
Variable x terms are   
  (-2x) + (5x)
= 3x

Variable y terms are   
  (2y) + (3y)
= 5y

Variable z terms are   
  (1z) + (2z)
= 3z

Constant  terms are   
  (1) + (7)
= 8


Hence the Equation is   3x+5y+3z=8
11
Add 2s-3t=2 and 5s-2t-12=0
7s-5t=14
Solution
(2s-3t=2) + ( 5s-2t-12=0 )
Variable s terms are   
  (2s) + (5s)
= 7s

Variable t terms are   
  (-3t) + (-2t)
= -5t

Constant  terms are   
  (2) + (12)
= 14


Hence the Equation is   7s-5t=14
12
Add 12y-15z=19 and 12y+13z=30
24y-2z=49
Solution
(12y-15z=19) + ( 12y+13z=30 )
Variable y terms are   
  (12y) + (12y)
= 24y

Variable z terms are   
  (-15z) + (13z)
= -2z

Constant  terms are   
  (19) + (30)
= 49


Hence the Equation is   24y-2z=49
13
Add 14y+2x-12z=14 and 16x+9y-2z=17
23y+18x-14z=31
Solution
(14y+2x-12z=14) + ( 16x+9y-2z=17 )
Variable y terms are   
  (14y) + (9y)
= 23y

Variable x terms are   
  (2x) + (16x)
= 18x

Variable z terms are   
  (-12z) + (-2z)
= -14z

Constant  terms are   
  (14) + (17)
= 31


Hence the Equation is   23y+18x-14z=31
14
Add 9a+8b+c=20 and 6a+6b+2c=-3
15a+14b+3c=17
Solution
(9a+8b+c=20) + ( 6a+6b+2c=-3 )
Variable a terms are   
  (9a) + (6a)
= 15a

Variable b terms are   
  (8b) + (6b)
= 14b

Variable c terms are   
  (1c) + (2c)
= 3c

Constant  terms are   
  (20) + (-3)
= 17


Hence the Equation is   15a+14b+3c=17
15
Add -12x+12y+3z=1 and 5x+13y+12z=70
-7x+25y+15z=71
Solution
(-12x+12y+3z=1) + ( 5x+13y+12z=70 )
Variable x terms are   
  (-12x) + (5x)
= -7x

Variable y terms are   
  (12y) + (13y)
= 25y

Variable z terms are   
  (3z) + (12z)
= 15z

Constant  terms are   
  (1) + (70)
= 71


Hence the Equation is   -7x+25y+15z=71
16
Add 3x+4y-5z=10 and 4x+5y-2z=20
7x+9y-7z=30
Solution
(3x+4y-5z=10) + ( 4x+5y-2z=20 )
Variable x terms are   
  (3x) + (4x)
= 7x

Variable y terms are   
  (4y) + (5y)
= 9y

Variable z terms are   
  (-5z) + (-2z)
= -7z

Constant  terms are   
  (10) + (20)
= 30


Hence the Equation is   7x+9y-7z=30
17
Add 3x+10y=1 and 13x+14y=18
16x+24y=19
Solution
(3x+10y=1 ) + ( 13x+14y=18 )
Variable x terms are   
  (3x) + (13x)
= 16x

Variable y terms are   
  (10y) + (14y)
= 24y

Constant  terms are   
  (1) + (18)
= 19


Hence the Equation is   16x+24y=19
18
Add -4y+5x+8z=9 and -4y-3x+2z=40
-8y+2x+10z=49
Solution
(-4y+5x+8z=9) + ( -4y-3x+2z=40 )
Variable y terms are   
  (-4y) + (-4y)
= -8y

Variable x terms are   
  (5x) + (-3x)
= 2x

Variable z terms are   
  (8z) + (2z)
= 10z

Constant  terms are   
  (9) + (40)
= 49


Hence the Equation is   -8y+2x+10z=49
19
Add 15x+12y=34 and 19x+12y=36
34x+24y=70
Solution
(15x+12y=34) + ( 19x+12y=36 )
Variable x terms are   
  (15x) + (19x)
= 34x

Variable y terms are   
  (12y) + (12y)
= 24y

Constant  terms are   
  (34) + (36)
= 70


Hence the Equation is   34x+24y=70
20
Add 15m-16n+3p=19 and 14m-16n+2p=0
29m-32n+5p=19
Solution
(15m-16n+3p=19) + ( 14m-16n+2p=0 )
Variable m terms are   
  (15m) + (14m)
= 29m

Variable n terms are   
  (-16n) + (-16n)
= -32n

Variable p terms are   
  (3p) + (2p)
= 5p

Constant  terms are   
  (19) + (0)
= 19


Hence the Equation is   29m-32n+5p=19

Worksheet: Algebraic Expressions Addition

Algebraic expressions addition worksheet is the largest collection of practice problems and solved exercises which can be served as homework, classwork or assignment problems for the students to learn, practice, assess, iterate and master the skills of how to solve such algebra problems in basic mathematics.

Online Test
00:00
Start my Challenge
Add 9p-8q=9 and 6p-6q=8
Add 10a+2b=10 and 2a+10b=10
Add 4m-6n=4 and 10m-4n=10
Add 9p+2q=8 and 2p+8q=9
Add 3x-5y=3 and 4x-4y=5
Add 8m-7n-8s=5 and 7m-8n-7s=8
Add 6m-6n-6s=3 and 6m-6n-6s=6
Add x+5y=5 and x+5y=8
Add 8p+4q=9 and 4p+9q=8
Add 5a-7b=5 and 4a-4b=7

Online Test: Algebraic Expressions Addition

This online test to find the algebraic expressions addition is a formative assessment which can be used as homework, classwork or assignment problems to assess and improve the learner's math skills on algebra.